2008
DOI: 10.1007/s12311-008-0011-6
|View full text |Cite
|
Sign up to set email alerts
|

Human cerebellar responses to brush and heat stimuli in healthy and neuropathic pain subjects

Abstract: Though human pain imaging studies almost always demonstrate activation in the cerebellum, the role of the cerebellum in pain function is not well understood. Here we present results from two studies on the effects of noxious thermal heat and brush applied to the right side of the face in a group of healthy subjects (Group I) and a group of patients with neuropathic pain (Group II) who are more sensitive to both thermal and mechanical stimuli. Statistically significant activations and volumes of activations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 135 publications
2
35
0
Order By: Relevance
“…Increased activation in lobules 3, 4 and Crus 2 was observed in this study. It is noteworthy that activation is observed in lobules 3, 4 (and 6) and Crus 2 in humans (Helmchen et al, 2003;Borsook et al, 2008).…”
Section: Brainstem Regionsmentioning
confidence: 86%
“…Increased activation in lobules 3, 4 and Crus 2 was observed in this study. It is noteworthy that activation is observed in lobules 3, 4 (and 6) and Crus 2 in humans (Helmchen et al, 2003;Borsook et al, 2008).…”
Section: Brainstem Regionsmentioning
confidence: 86%
“…Recently, different regions of the cerebellum have been shown to be linked to several RSN. In particular, crus I have been shown to be linked to the salience network and ECN (Borsook et al, 2008, Caulfield et al, 2015). Our study showed that both the salience network and ECN have altered connectivity in SCD patients, and so this might also explain the negative connectivity in the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo PET studies in rhesus monkeys show that [ 11 C]MK-4232 penetrates the blood-brain barrier (BBB) rapidly, with (Weiller et al, 1995;Bahra et al, 2001), and recent studies indicate that the cerebellum might have a role in nociception and migraine (Vincent and Hadjikhani, 2007;Borsook et al, 2008;Moulton et al, 2010). Spreading depression, cerebellar dysfunction, and familial hemiplegic migraine have also suggested a connection between the cerebellum and migraines.…”
Section: Discussionmentioning
confidence: 99%